Удосконалення якості виготовлення автобусних панелей на електрогідравлічних пресах - Тараненко, Михайло (Видавництво Львівської політехніки, 2018)
The experience of applying the electro-hydraulic (EG) forming processes for the manufacturing of aircrafts and vehicles parts is known. In general, the experience is positive, but not all the advantages of such forming can be realized in practice. The analysis is carried out and not full implementation of these processes is done. It is shown that underdeveloped manufacturability of auto-body panels for EG-punching takes place.
Improvement of the quality of manufacturing of bus panels on electrohydraulic presses
Keywords: 621.983.044.4